Settings and Interpretation: ‘Umfelder’ and ‘Verstehen’. Text Linguistics from a Coserian Perspective - Willems, Klaas (Acta Universitatis Danubius. Communicatio, 2022)
E. Coseriu’s seminal article ‘Determinación y entorno’ (1955-1956) introduces a complex matrix of settings (‘Umfelder’) that is intended to serve as a framework for the analysis of all kinds of text and discourse. Coseriu’s framework differentiates between ‘situation’, ‘region’, various ‘contexts’ and ‘universe of discourse’. In order to determine the role of each setting in the interpretation of a specific text, the paper provides a detailed analysis of an editorial cartoon. The paper concludes by pointing out the complementarity of Coseriu’s framework with alternative approaches to texts and discourse such as D. Hymes’ ethnographic SPEAKING model and the (Neo-)Gricean theory of conversational implicatures.